UNDIFFERENTIATED CARCINOMA WITH OSTEOCLAST-LIKE GIANT CELLS (UC-OGC) OF THE HEAD OF PANCREAS: CARCINOMA INDIFERENCIADO CON CÉLULAS GIGANTES DE TIPO OSTEOCLASTOS EN LA CABEZA DE PÁNCREAS - Palomino, Eugenio (2019)
Undifferentiated carcinoma with undifferentiated osteoclast-like cells (UC-OGC) in the head of the pancreas is extremely rare. The clinicalpathological, imaging and topographic appearance characteristics are not wellclassified. This case report describes a patient with UC-OGC of the Pancreas Head. Our patient, an adult over 75 years of age, had a considerable illness time, without relevant symptoms until the advanced stages of the tumor, debuting with shallow gastric discomfort, then weight loss. In the diagnostic tests they found the presence of a tumor that compromised the stomach, duodenum and pancreas. The definitive diagnosis was given by the pathological study. There are not enough clinical data available for a treatment that guarantees a higher survival rate in patients, however, pancreatoduodenectomy is currently the alternative that offers the best results, on the other hand, the prognosis after surgery and the recurrence rate still uncertain.